2012
DOI: 10.1016/j.neurobiolaging.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain-dominant deficit in cerebrovascular reactivity in Alzheimer's disease

Abstract: Epidemiologic evidence and postmortem studies of cerebral amyloid angiopathy suggest that vascular dysfunction may play an important role in the pathogenesis of Alzheimer's Disease (AD). However, alterations in vascular function under in vivo conditions are poorly understood. In this study, we assessed cerebrovascular-reactivity (CVR) in AD patients and age-matched controls using CO2-inhalation while simultaneously acquiring Blood-Oxygenation-Level-Dependent (BOLD) MR images. Compared to controls, AD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 48 publications
9
125
2
Order By: Relevance
“…This agrees with previous studies reporting abnormal CVR in the frontal lobe of patients (Cantin et al, 2011;Yezhuvath et al, 2012). Because the amplitude of cerebral blood flow in the frontal lobe is not significantly different between control subjects and patients under CO 2 challenge (Cantin et al, 2011;Oishi et al, 1999), this velocity difference could be functionally relevant in cognitive performance.…”
Section: Cvr Velocity and Cognitive Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with previous studies reporting abnormal CVR in the frontal lobe of patients (Cantin et al, 2011;Yezhuvath et al, 2012). Because the amplitude of cerebral blood flow in the frontal lobe is not significantly different between control subjects and patients under CO 2 challenge (Cantin et al, 2011;Oishi et al, 1999), this velocity difference could be functionally relevant in cognitive performance.…”
Section: Cvr Velocity and Cognitive Performancesupporting
confidence: 92%
“…In that study, however, the spatial distribution of these changes in timing was not studied, and no relationship between cognition and velocity was established. Other studies suggest that changes in the amplitude of CVR in AD is widely distributed across the brain: impaired CVR in frontal, parietal, and temporal lobes has been found using CT (Oishi et al, 1999), and BOLD-MRI studies (Cantin et al, 2011;Yezhuvath et al, 2012) showing that large-scale vascular changes are occurring with the disease. Coherently, resting-state BOLD fMRI investigations also demonstrated large-scale functional network alterations in dementia (Greicius et al, 2004), suggesting that studying regional changes across the whole brain yields additional insights into the spatial localization of differences between patients and control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for the RSFA approach (Kannurpatti et al, 2014), which we found to not be uniformly associated with standard CVR estimates. We argue the same for our parametricdeconvolution-based rs-qCVR estimates, as in many cases, such as in stroke ) and Alzheimer's disease (Silvestrini et al, 2006;Yezhuvath et al, 2012), CVR maps are used to depict local abnormalities rather than make statements regarding global differences between individuals. In such cases, it is more crucial that the spatial pattern rather than the absolute value of the CVR estimates be accurate, and therefore, calibration of the rs-fMRI CVR values is not necessary.…”
Section: Practical Considerations and Limitationsmentioning
confidence: 91%
“…Each participant underwent MRI‐BOLD sequences with CVR hypercapnia measurements according to the methods developed previously 22, 36. Hypercapnia was induced via a Douglas bag alternating between a flow of room air and 5% carbon dioxide (CO 2 ) mixed with room air every minute for 7 min total while the MRI‐BOLD images were acquired.…”
Section: Methodsmentioning
confidence: 99%